2018
DOI: 10.36685/phi.v4i3.209
|View full text |Cite
|
Sign up to set email alerts
|

The Behavior of Foot Care in Patients With Type 2 Diabetes Mellitus: Applying the Theory of Planned Behaviour

Abstract: Background: Diabetes mellitus (DM) is a chronic non-infectious disease with complications such as diabetic foot, which has the potential for amputation if left untreated. Theory of Planned Behavior (TPB) is a behavior-based theory that can be applied to DM patients including foot care to minimize risk. Some studies related to TPB particularly about physical activity and diet have been explored, however, studies on foot care are still lacking.Objective: This study aims to apply the Theory of Planned Behavior (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
1
4
0
2
Order By: Relevance
“…It shows that some respondents aged 46 years had high blood sugar. This was in line with the results of other studies that show that most respondents with diabetes mellitus aged ³46 years with an average age of 53 years, and there was a relationship between age and the incidence of diabetes mellitus (Narmawan, Syahrul, & Erika, 2018;Rahayu et al, 2012). Basic health research also shows that the incidence of DM increases with age even though > 75 years old and the prevalence of events begins to decrease (Ministry of Health, 2018).…”
Section: Blood Sugar Content Based On Muna Tribe Community's Charactesupporting
confidence: 91%
“…It shows that some respondents aged 46 years had high blood sugar. This was in line with the results of other studies that show that most respondents with diabetes mellitus aged ³46 years with an average age of 53 years, and there was a relationship between age and the incidence of diabetes mellitus (Narmawan, Syahrul, & Erika, 2018;Rahayu et al, 2012). Basic health research also shows that the incidence of DM increases with age even though > 75 years old and the prevalence of events begins to decrease (Ministry of Health, 2018).…”
Section: Blood Sugar Content Based On Muna Tribe Community's Charactesupporting
confidence: 91%
“…It is described as a person's subjective evaluation or past experience towards an intended behaviour based on the expected outcome from the particular behaviour (Erten, 2018;Lang, 2018). Likewise, TPB has been widely applied on health related programs/ interventions to study a person's cognition response and to provide an intensive understanding of the reasons why a person performs or fails to perform that specific behavioural tendency (Kopelowicz et al, 2015;Mutua, Pertet, & Otieno, 2017;Narmawan, Syahrul, & Erika, 2018). Empirical studies reviewed that, a person are likely to engage into a particular behaviour only if, he/she perceives it as favourable (positive outcome expectancy) and vice versa (Kalolo & Kibusi, 2015;Leske, Strodl, & Hou, 2017;Mtenga, Exavery, Kakoko, & Geubbels, 2015).…”
Section: Theory Of Planned Behaviourmentioning
confidence: 99%
“…Foot Self-Care Behavior Assessment Form: This form was created based on a search of the relevant literature by the researchers to evaluate the foot self-care practices of individuals with Type-2 DM (Embil et al, 2018;D'Souza et al, 2017;Narmawan et al, 2018;Schaper et al, 2019;Wendling & Beadle, 2015). The final version of the form was created after taking the opinions of five public health nursing experts.…”
Section: Personal Information Formmentioning
confidence: 99%
“…It is clear that individuals with diabetes should perform regular foot self-care to minimize diabetic foot complications. A study on DFD found that a majority of the participants had a positive attitude and practiced behavioral controls on diabetic foot self-care (Narmawan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%